COMMITMENT OF LOCAL GOVERNMENT IN PROVIDING LEGAL AID FOR THE POOR SOCIETY - Saru Arifin (Jurnal Dinamika Hukum, 2016)
The birth of the Legal Aid Act in the year of 2011 had strengthened the right of legal assistance for the poor in resolving legal issues that arrise. In the Act, Local Goverment is given the authority to provide legal assistance. This study uses socio-juridical method that aims to analyze the commitment of the local government of Badung regency, Bali, as one of the region with the highest revenue in Indonesia, in providing legal assistance. These results indicate that high local revenue of Badung regency, Bali are not positively correlated with the commitment to provide the legal assistance to the poor. This is indicated by the absence of a Local Regulation on legal aid and no funds were allocated to help the poor who need legal help. In addition, in the implementation of legal aid in Badung there are two main obstacles that the lack of regulation of legal aid and the constraints the letter to residents from outside the area. Keywords: Legal Aid, poor people, Justice, Legal Aid Institute